The Paradox of Digital Transformation: Human Resource Readiness in Artificial Intelligence-Based Human Resource Management - Achmad Singgih Laksono; Hwihanus (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The impact of digitalization has brought significant changes to human resource management and human resources management (HRM). This study focuses on the paradox of digital transformation, a situation where technological advances and Artificial Intelligence offer high efficiency, but success remains highly dependent on human resource readiness. This study uses a qualitative approach with a literature review method. The results of the study indicate that the failure of digital transformation is not solely caused by technological limitations, but rather by the low cognitive, psychological, and work culture readiness of human resources. The rapid management of the latest technology in the form of AI and digitalization will offer significant efficiency and convenience. However, successful implementation is highly dependent on human resource readiness. This phenomenon shows that failure in the digital era is not only caused by technological limitations, but also by the unpreparedness of human resources to adapt (Davenport & Westerman, 2018). This study contributes by identifying the paradox between technological advances and human resource readiness in digital transformation.